Post-Appendectomy Complication: Peritonitis and Abscess Due to Partial Obstructive Ileus in a Patient with Neglected Appendicitis - Christiny, Christiny; Putu Rangga Rasnadea Tama, I; Agung Gede Agung Budhi Kusuma, Anak (Journal of Comprehensive Science, 2024)
A 13-year-old male presented with abdominal pain, fever, and vomiting two weeks after open appendectomy for neglected appendicitis. Examination revealed peritonitis signs, including diffuse tenderness. Laboratory findings showed leukocytosis and elevated C-reactive protein (CRP), indicating inflammation. Abdominal X-rays suggested dynamic ileus, while contrast-enhanced CT revealed pelvic fluid collections, gas-forming abscesses, partial ileus, and pneumoperitoneum, consistent with peritonitis complications. Complications such as adhesive small bowel obstruction (SBO), abscess formation, and peritonitis can arise after appendectomy. Adhesions from surgery may cause partial ileus, obstructing bowel motility, while infection can lead to abscesses. Imaging, particularly contrast-enhanced CT, is vital for accurate diagnosis and intervention. Treatment involves surgical drainage of abscesses, adhesiolysis, and broad-spectrum antibiotics to control infection. In this case, timely surgical and medical management resulted in a successful outcome. Peritonitis following appendectomy for neglected appendicitis can result in partial obstructive ileus and abscess formation, underscoring the need for vigilance during postoperative follow-up. Early imaging and intervention are critical to prevent severe outcomes. Prompt surgical and medical treatment enables full recovery, emphasizing the importance of recognizing post-appendectomy complications.